The Potency of Inulin Extraction Waste Fermentation From Local Tubers as a Feed Additive - Septian, Mohamad Haris; Suhendra, Danes; Sihite, Mikael; Saputri, Dyah Eka (Fakultas Peternakan, Universitas Padjadjaran, 2026)
This study aims to determine the potential of inulin extraction waste fermentation as a feed additive based on the content of lactic acid, dry matter, pH, and Fleigh points. This research was conducted from March to June 2022 at the Animal Husbandry and Fisheries Laboratory, Tidar University. The experimental design used in this study was a Completely Randomized Design with 4 treatments (fermentation of inulin extraction waste: T1 Dioscorea alata (uwi), T2: ganyong (Dioscorea alata discolor), T3: gadung(Dioscorea hispida), and T4: umbi ungu (Ipomoea batatas). Each treatment was replicated 5 times. The variables observed were lactic acid content, dry matter, crude protein, pH, and Fleigh points of inulin extraction waste fermentation. The Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan's multiple range test if the results were significantly different. The data were analyzed using IBM SPSS 21. Inulin extract wastes from local tubers significantly affected (p<0.05) lactic acid content, pH, and Fleigh points, but not significantly affected (p>0.05) the dry matter content. T3 and T4 produced the highest lactic acid content, Fleigh points, and the lowest pH value.